2004
DOI: 10.1097/00002030-200411190-00007
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of emtricitabine and lamivudine in stably suppressed patients with HIV

Abstract: In stably suppressed patients, 200 mg emtricitabine QD was equivalent to 150 mg lamivudine BID. Emtricitabine-containing HAART was associated with a high rate of sustained virologic suppression during 4 years of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 5 publications
2
41
1
Order By: Relevance
“…Immunological testing indicated an increased CD4 cell count in both naïve and experienced patients (mean change: 50-200 cells/mm 3 ). These findings are similar to the results of previous reports [11][12][13], and this study provides evidence that cART containing FTC and TDF is effective in controlling symptoms both virologically and immunologically in Japanese patients infected with HIV-1.…”
Section: Discussionsupporting
confidence: 92%
“…Immunological testing indicated an increased CD4 cell count in both naïve and experienced patients (mean change: 50-200 cells/mm 3 ). These findings are similar to the results of previous reports [11][12][13], and this study provides evidence that cART containing FTC and TDF is effective in controlling symptoms both virologically and immunologically in Japanese patients infected with HIV-1.…”
Section: Discussionsupporting
confidence: 92%
“…Given the greater activity and longer intracellular half-life of FTC compared with 3TC, these small differences in FC are unlikely to be clinically significant. In a clinical study of FTC versus 3TC in treatment-experienced patients (Benson et al, 2004), no differences were observed in the number of patients experiencing virological failure between the two arms; only the M184V mutation was significantly associated with virological failure in this study (Van der Horst C, Quinn JB, Hinkle J, Bae A, Borroto-Esoda K, Moxham C, Rousseau F. Predictors of virologic failure in HIV-1 infected adults on a stable lamivudine HAART regimen. 42nd Annual Interscience Conference on Antimicrobial Agents andChemotherapy.…”
Section: Discussionmentioning
confidence: 56%
“…7 In adult patients, FTC demonstrated significantly greater viral suppression than 3TC in a short-term monotherapy study and displayed antiviral equivalence to 3TC when administered as part of a combination antiretroviral regimen. 8,9 Virologic response to FTC was superior to stavudine (d4T) when either agent was administered in combination with efavirenz (EFV) and enteric-coated didanosine (ddI EC). 10 The efficacy of a once-daily regimen including FTC, ddI EC, and EFV was confirmed in adults both in a pilot study and a randomized, open-label trial.…”
Section: Efficacymentioning
confidence: 99%
“…3 In comparator trials, reports of adverse reactions were similar between FTC and 3TC but were less common with FTC compared to d4T. [8][9][10] In adults, grade 3 and 4 laboratory abnormalities were also similar to those of 3TC and d4T during combination therapy. 6,7,14 Most common (occurring in > 5% of patients) were increased creatinine kinase, triglycerides, hepatic transaminases, and serum amylase, and decreased neutrophil counts.…”
Section: Adverse Drug Reactionsmentioning
confidence: 99%